DSC764: Operations Analytics / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (Universiti Teknologi MARA (UiTM), 2017)
This course is designed to impact the way of thinking about transforming data into better decisions. Recent extraordinary improvements in data-collecting technologies have changed the way firms make informed and effective business decisions. This course focuses on how the data can be used to profitably match supply with demand in various business settings. The students will be taught on how to model future demand uncertainties, how to predict the outcomes of competing policy choices and how to choose the best course of action in the face of risk. In addition, this course will utilize the latest operations analytics tools to drive a good operational outcomes and deliver results that are both definitive and measurable.